A new, recently extinct subspecies of the Kuroiwa’s Leopard Gecko, Goniurosaurus kuroiwae (Squamata: Eublepharidae), from Yoronjima Island of the Ryukyu Archipelago, Japan - Yasuyuki Nakamura (Acta Herpetologica, 2014)
A new subspecies of the eublepharid gecko, Goniurosaurus kuroiwae, is described on the basis of fragmentary bones recovered from a midden on Yoronjima Island, Ryukyu Archipelago, Japan. It differs from the other conspecific subspecies in having a unique combination of osteological character states: in particular, the maxilla contains a posteriorly extended maxillary shelf and a scarcely inclined lateral wall above the posterior tooth row, and the frontal contains a widened anterior section and a laterally overhanging anterior part of lateral prefrontal facet, both of which differentiate this new subspecies from the morphologically most similar G. k. kuroiwae. The new subspecies, endemic to Yoronjima Island, may have gone extinct, together with several other amphibians and reptiles on the island — most likely due to human-related deforestation and increased predation pressure from introduced weasels.